Experimental study of the pressure loss in aero-engine air-oil separators - Cordes, A. Laura; Pychynski, B. Tim; Schwitzke, C. Corina; Bauer, D. Hans-Jörg; de Carvalho, A. Thiago P.; Morvan, B. Hervé P. (Cambridge University Press, 2017)
The results of extensive experimental testing of an aero-engine air-oil separator are presented and discussed. The study focuses on the pressure loss of the system. Oil enters the device in the form of dispersed droplets. Subsequently, separation occurs by centrifuging larger droplets towards the outer walls and by film formation at the inner surface of a rotating porous material, namely an open-cell metal foam. The work described here is part of a study led jointly by the Karlsruhe Institute of Technology (KIT) and the University of Nottingham (UNott) within a recent EU project. The goal of the research is to increase the separation efficiency to mitigate oil consumption and emissions, while keeping the pressure loss as low as possible. The aim is to determine the influencing factors on pressure loss and separation efficiency. With this knowledge, a correlation can eventually be derived. Experiments were conducted for three different separator configurations, one without a metal foam and two with metal foams of different pore sizes. For each configuration, a variety of engine-like conditions of air mass flow rate, rotational speed and droplet size was investigated. The experimental results were used to validate and improve the numerical modelling. Results for the pressure drop and its dependencies on air mass flow rate and the rotational speed were analysed. It is shown that the swirling flow and the dissipation of angular momentum are the most important contributors to the pressure drop, besides the losses due to friction and dissipation caused by the flow passing the metal foam. It was found that the ratio of the rotor speed and the tangential velocity of the fluid is an important parameter to describe the influence of rotation on the pressure loss. Contrary to expectations, the pressure loss is not necessarily increased with a metal foam installed.